2020
DOI: 10.1101/2020.05.07.083246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shoot and root thermomorphogenesis are linked by a developmental trade-off

Abstract: Temperature is one of the most impactful environmental factors to which plants adjust their growth and development. While the regulation of temperature signaling has been extensively investigated for the aerial part of plants, much less is known and understood about how roots sense and modulate their growth in response to fluctuating temperatures. Here we found that shoot and root growth responses to high ambient temperature are coordinated during early seedling development. A shoot signaling module that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Surprisingly, we found that CAB3p : DOF-HY5 could also rescue the hy5 root growth defects ( Figure 2D ), indicating that HY5 mobility is not required for HY5-dependent shoot-to-root communication. These results are consistent with the finding that HY5 can trigger an unknown signal in the shoot to control root thermomorphogenesis ( Gaillochet et al, 2020 ). HY5 expression in the shoot and the root was weaker in CER6p : DOF-HY5 line number 9 than that in other lines derived from this construct ( Figure 1D and Supplemental Figure 3A ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, we found that CAB3p : DOF-HY5 could also rescue the hy5 root growth defects ( Figure 2D ), indicating that HY5 mobility is not required for HY5-dependent shoot-to-root communication. These results are consistent with the finding that HY5 can trigger an unknown signal in the shoot to control root thermomorphogenesis ( Gaillochet et al, 2020 ). HY5 expression in the shoot and the root was weaker in CER6p : DOF-HY5 line number 9 than that in other lines derived from this construct ( Figure 1D and Supplemental Figure 3A ).…”
Section: Resultssupporting
confidence: 92%
“…In addition to the communication between shoot cell layers, communication between aerial and underground organs is crucial for coordinating growth and development between these tissues ( van Gelderen et al, 2018b ). Disrupting this communication by severing aerial and underground portions of a plant leads to decreased growth of both the shoot and roots, and the accumulation of chlorophyll in roots ( Kobayashi et al, 2017 ; Bellstaedt et al, 2019 ; Gaillochet et al, 2020 ). However, as mechanical perturbations are quite severe, the combined effects of the wounding response and the loss of all mobile signals make specific effects difficult to discern.…”
Section: Introductionmentioning
confidence: 99%